Kedudukan Hukum dan Hak Waris Anak Hasil Inseminasi Buatan di Indonesia - Rahakbauw, Frets Paulus; Ahmad, Moh Jufri (CV. Era Digital Nusantara, 2024)
Artificial insemination has become a crucial option for couples facing conceptual challenges of infertility. The intricate process of in vitro fertilization adds further complexity when involving the use of donor sperm and embryo transplantation into a surrogate mother's womb. This research aims to explore relevant aspects of national and Islamic law in this context, with a specific emphasis on debates surrounding the legal status of children produced through assisted reproductive techniques. The research methodology adopts a normative juridical approach, conducting in-depth analyses of relevant literature and secondary data. The findings highlight that issues related to child legal status involve internal family dynamics. Despite existing regulations such as the Indonesian Health Law Number 17 of 2023, Government Regulation Number 14 of 2014 on Reproductive Health, and Minister of Health Decree Number 039/MENKES/SK/I/2010, their scope remains limited to legally married couples. From an Islamic legal perspective, the study sharply delves into the legitimacy of children born through artificial insemination by interpreting the Qur'an and Hadiths. The presented arguments aim to formulate a basis of support for the recognition of the legal status of such children. Therefore, the research emphasizes the urgency of establishing specific legislation regulating Test-Tube Babies and its legal aspects by the Government to provide legal clarity regarding the status and inheritance rights of children born through artificial insemination, aligning with Islamic legal principles. This study underscores the necessity for the development of a more holistic and responsive legal policy to address the complex issues arising from advancements in reproductive technology. By contributing to legal policy formulation, it is hoped that this research will pave the way for more comprehensive and responsive regulations to meet the needs of communities grappling with infertility challenges.